Effects of acid rain on growth, photosynthesis and soil properties of Zea mays in a controlled pot study - Mohamad Hilmi, Ibrahim; MUHAMMAD AIMAN HAKIM, AHMAD FAIZ; ESMERELDA JOSELIN, TAIT; SHARIFAH ZILA SYAHIDA, WAN ALIAS (ISP Management (M) Sdn Bhd / Incorporated Society of Planters, 2025)
This study examined the effects of simulated acid rain (SAR) on the growth, photosynthetic performance, and soil properties of maize (Zea mays) in a controlled pot experiment. Six treatments, including the control, were applied with SAR pH levels ranging from 3.5 to 5.5, while the control was treated with rainwater (pH 6.0). Photosynthetic performance was assessed using a portable open-flow gas exchange system under two temperature and CO2 activation conditions, while soil properties were analysed using a CHNS Analyser and pH meter, with total acidity and exchangeable acidity was determined by the double titration method. Maize plants subjected to lower pH level (3.5 and 4.0) treatments exhibited significant reductions, relative to the control, in plant height, stem diameter, and height increment, indicating impaired growth. Photosynthetic efficiency, measured through net CO2 assimilation rates and water use efficiency, declined under more acidic conditions, reflecting physiological stress. Soil analysis revealed a decrease in pH and increased acidity, with notable changes in total acidity and exchangeable hydrogen. While soil carbon, nitrogen, and hydrogen content remained stable, sulphur content varied, suggesting a plausible role of sulphuric acid in soil acidification. The results highlighted the detrimental effects of acid rain on maize growth and soil health, with implications for agricultural productivity in regions prone to acid deposition. Strategies to mitigate the impacts, such as soil pH management and improved agricultural practices, are proposed to sustain crop yields and soil fertility under acid deposition condition.